A Prospective Study of Macrophage Inhibitory Cytokine-1 (MIC-1/GDF15) and Risk of Colorectal Cancer - Mehta, Raaj S. (Oxford University Press, 2014)
BACKGROUND: Chronic inflammation plays a role in the development of colorectal cancer (CRC). The novel plasma inflammatory biomarker macrophage inhibitory cytokine-1 (MIC-1, GDF15) may have a direct mechanistic role in colorectal carcinogenesis. METHODS: We conducted a prospective, nested, case–control study of incident CRC among men and women who provided a prediagnostic blood specimen. We used an enzyme-linked immunosorbent assay to measure MIC-1 and examined associations between quintiles of MIC-1 and CRC using logistic regression adjusted for matching factors (age and date of blood draw), risk factors, and other plasma inflammatory markers. We also assessed the relationship between MIC-1 levels and prostaglandin-endoperoxide synthase 2 (PTGS2)/cyclooxygenase-2 (COX-2) enzyme status in tumors with available tissue for analysis. All statistical tests were two-sided. RESULTS: Compared with men and women within the lowest quintile of plasma MIC-1, the multivariable relative risk (RR) for CRC was 1.93 (95% confidence interval [CI] = 1.27 to 2.94) for the highest quintile (P (linear trend) = .004). In an exploratory analysis, we found that among individuals with high plasma MIC-1 levels (quintiles 2–5), compared with nonuse, regular use of aspirin and nonsteroidal anti-inflammatory drugs (NSAIDs) was associated with a lower risk of PTGS2-positive CRC (multivariable RR = 0.60; 95% confidence interval = 0.41 to 0.88) but not PTGS2-negative CRC (multivariable RR = 1.21; 95% CI = 0.71 to 2.07). In contrast, among individuals with low MIC-1 levels (quintile 1), aspirin and NSAID use was not associated with a lower risk of PTGS2-positive CRC (multivariable RR = 0.57; 95% CI = 0.21 to 1.54) or PTGS2-negative CRC (multivariable RR = 1.41; 95% CI = 0.47 to 4.23). CONCLUSIONS: Our results support an association between higher levels of circulating MIC-1 (GDF15) and CRC. Aspirin/NSAID use appeared to lower risk of PTGS2-positive cancers, particularly among individuals with high levels of circulating MIC-1.